PENGEMBANGAN MODEL LATIHAN KECEPATAN PUSH-UP TERHADAP PUKULAN GYAKU TSUKI ATLET KARATE - Moh Sahruk Latif, Sahruk; Ucok Hasian Refiater; Suprianto Kadir; Meri Haryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop and test the effectiveness of a varied push-up training model in improving the speed of gyaku tsuki punches among karate athletes in Gorontalo City. The research method used is Research and Development (R&D) applying the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects involved cadet and junior category karate athletes divided into small and large groups. Data collection instruments included validation sheets for media experts, material experts, and physical condition experts, as well as gyaku tsuki punch speed tests conducted before and after treatment. Data analysis used normality tests, homogeneity tests, and paired t-tests to observe mean differences. The results showed that the developed training model was rated as highly valid, practical, and feasible for use by experts. Effectiveness test results proved a very significant improvement (p < 0.01) in punch speed after implementing the training model. The conclusion of this study is that the developed push-up training model effectively improves arm muscle explosive power, coordination, and movement speed, thus it can be recommended as a training guide for karate coaches and athletes to enhance gyaku tsuki punch performance. Keywords: Development, Push-Up Training Model, Punch Speed, Gyaku Tsuki, Karate.